Towards a Dynamic Spatial Microsimulation Model for Projecting Auckland's Spatial Distribution of Ethnic Groups - Mohana Mondal; Michael P. Cameron; Jacques Poot (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2023)
In this paper we describe the development, calibration and validation of a dynamic spatial microsimulation model for projecting small area (area unit) ethnic populations in Auckland, New Zealand's most culturally diverse city, in which about 40 percent of the population is foreign born. The key elements of the microsimulation model are a module that projects residential mobility within Auckland and migration between Auckland and the rest of the world, and a module that projects mobility in ethnic identity. The model is developed and calibrated using data on 1996-2001 linked populations in the New Zealand Longitudinal Census (NZLC) 1981-2006. We compare the microsimulation results with the actual 2006 population in each area unit. We find that in terms of indexes of overall residential sorting and ethnic diversity, our projected values are very close to the actual values. At a more disaggregated spatial scale, the model performs well in terms of the simulated normalised entropy measure of ethnic diversity in area units, but performs less well in terms of projecting residential sorting for each individual ethnic group.
Keywords: C53; F22; J10; R23; 330; dynamic microsimulation model; ethnic identity; location transition; ethnic transition